Effect of saffron supplementation on oxidative stress markers (MDA, TAC, TOS, GPx, SOD, and pro-oxidant/antioxidant balance): An updated systematic review and meta-analysis of randomized placebo-controlled trials - Abedi, Ali; Ghobadi, Hassan; Sharghi, Afshan; Iranpour, Sohrab; Fazlzadeh, Mehdi; Aslani, Mohammad Reza (Frontiers in Medicine, 2023)
Introduction This study aimed to perform an updated systematic review and meta-analysis to evaluate the effectiveness of saffron supplementation on oxidative stress markers [malondialdehyde (MDA), total antioxidant capacity (TAC), total oxidant status (TOS), glutathione peroxidase (GPx), superoxide dismutase (SOD), and prooxidant/antioxidant balance (PAB)] in randomized controlled trials (RCTs). Methods We searched PubMed/Medline, Web of Science, Scopus, Cochrane CENTRAL, and Google Scholar until December 2022. Trial studies investigating the effects of oral saffron supplements on MDA, TAC, TOS, GPx, SOD, and PAB concentrations were included in the study. To analyze the results, mean differences (SMD) and 95% confidence intervals (CI) were pooled using a random effects model. Heterogeneity was assessed using the Cochrane Q and I2 values. Sixteen cases were included in the meta-analysis (468 and 466 subjects in the saffron and control groups, respectively). Results It was found that saffron consumption caused a significant decrease in MDA (SMD: −0.322; 95% CI: −0.53, −0.16; I2 = 32.58%) and TOS (SMD: −0.654; 95% CI: −1.08, −0.23; I2 = 68%) levels as well as a significant increase in TAC (SMD: 0.302; 95% CI: 0.13, 0.47; I2 = 10.12%) and GPx (SMD: 0.447; 95% CI: 0.10, 0.80; I2 = 35%). Subgroup analysis demonstrated a significant reduction in MDA levels in studies with a saffron dosage of >30 mg/day, age of <50 years, and study duration of <12 weeks. Among the limitations of the study, we can point out that the studies were from Iran, the different nature of the diseases included, and were not considered of some potential confounders such as smoking, physical activity, and diet in the studies. Discussion In summary, the results showed that saffron has beneficial effects on oxidative stress markers.